Association between dental caries and body mass index in 12–15 year old private school children in Ibadan, Nigeria. Issue 1 (April 2016) - Denloye, Obafunke; Popoola, Bamidele; Ifesanya, Joy
Abstract: Purpose: The study aimed to determine dental caries prevalence among a representative sample of 12–15 year old private secondary school students in Nigeria and compare the association of dental caries with body mass index in this sample. Method: A sample of five hundred and ninety five 12–15 year old students was selected using a proportionate sampling method from a cross section of private secondary schools. Clinical recording of dental caries was done according to WHO diagnostic criteria and BMI percentile was calculated based on age and gender from the weight and height of each child. Data generated was analysed with SPSS version 20.0 and statistical tests used were t test, ANOVA and chi test. A p value < 0.05 was considered statistically significant. Results: Caries prevalence was 16% with a mean DMFT value of 0.27 ± 0.83. The Male: Female mean DMFT value was found to be significantly equal at 14 years. Majority of the children had normal BMI. The BMI and DMFT relationship did not follow a trend but a significant finding was observed at age 15 years although regression analysis did not show any correlation between the two indices. Conclusion: The study showed a higher caries prevalence with majority of the children having normal BMI. No conclusive relationship was found between DMFT and BMI in the studied student population. The need for continuous caries preventive program is emphasized.